623. Preliminary Dosing for Adolescent Hematopoietic Stem-Cell Transplant (HSCT) Recipients Based on Pharmacokinetic (PK), Safety, and Efficacy Data of Letermovir (LET) for Cytomegalovirus (CMV) Prophylaxis. (15th December 2022) - Groll, Andreas H; Schulte, Johannes H; Antmen, Ali Bulent; Fraser, Christopher J; Teal, Valerie L; Haber, Barbara A; Caro, Luzelena; McCrea, Jacqueline B; Fancourt, Craig; Menzel, Karsten; Badshah, Cyrus
Abstract: Background: LET is a CMV terminase complex inhibitor approved for prophylaxis of CMV infection and disease in adult CMV-seropositive allogeneic HSCT recipients. Objectives of this ongoing study are to evaluate PK, safety, and efficacy of LET for CMV prophylaxis in adolescent allogeneic HSCT recipients (aged 12 to < 18 years). Methods: This is a Phase 2b nonrandomized, multicenter, open-label, sequential dose escalation study (NCT03940586). Participants (pts) were divided into 3 age groups, the oldest (AG1) comprising adolescents. AG1 pts received the recommended adult 480 mg LET dose (240 mg with cyclosporine A [CsA]) once-daily orally (PO) or intravenously (IV). Pediatric target exposures were based on model-predicted Phase 3 population PK simulations for adult HSCT recipients: 16, 900 h.ng/mL (480 mg PO without [w/o] CsA) to 147, 800 h.ng/mL (480 mg IV w/o CsA). PK parameters were determined by non-compartmental analysis for 14/28 AG1 pts. Results: All 28 AG1 pts enrolled were CMV-seropositive (median age: 13.5 [range, 12–17] years; median weight: 53.8 [range, 28.7–95.0] kg; White: 53.6%). PK (N=14): Of 13 evaluable AG1 pts (weight, 30.4–87.7 kg), 8 received 480 mg LET alone (oral/IV; Table 1 ); 6/8 achieved exposures within the target range and 2/8 (oral, n=1; IV, n=1) achieved exposures above the target range but below the maximum observed in the development program. 5 AG1 pts received 240 mg LET (oral/IV) with CsA; 5/5 achieved exposures within the target range. Safety (N=28) : No major safety concerns were reported for AG1 pts receiving LET, similar to the adult LET safety profile. Efficacy (N=25) : The proportion of AG1 pts receiving LET with clinically significant CMV infection (CMV disease/pre-emptive treatment for CMV viremia) through week 24 post-HSCT was similar (24%) to that for adults receiving LET in the pivotal Phase 3 study (37.5%). Conclusion: Administration of adult LET doses for CMV prophylaxis post-HSCT in this adolescent cohort resulted in exposures within the development program safety margins, and was associated with similar efficacy and safety to LET use in adult patients. Preliminary results support 480 mg (240 mg with CsA) as an oral and IV LET dose in adolescent HSCT recipients, with a final dose recommendation after study completion. Disclosures: Andreas H. Groll, MD, Amplyx, Astellas, Basilea, F2G, Gilead Sciences, Merck Sharp & Dohme, and Pfizer: Advisor/Consultant|Astellas, Basilea, F2G, Gilead Sciences, Merck Sharp & Dohme, and Pfizer: Served at the speakers' bureau|Gilead Sciences, Merck Sharp & Dohme, and Pfizer: Grant/Research Support Johannes H. Schulte, MD, German Cancer Consortium (DKTK): Support by Ali Bulent Antmen, MD, PhD, Novo Nordisk, Pfizer, Roche, Takeda: Advisor/Consultant Valerie L. Teal, MS, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee Barbara A. Haber, MD, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee Luzelena Caro, PhD, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee Jacqueline B. McCrea, PharmD, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee Craig Fancourt, PhD, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee Karsten Menzel, PhD, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee Cyrus Badshah, MD, PhD, Merck & Co., Inc.: Stocks/Bonds|Merck Sharp & Dohme LLC: Current or former employee.